Student response to the radec learning model in improving teacher pedagogic competence - Trisna Nugraha; Sofyan Nur Mahardhika (xxxx-xxxx, 2023)
Pedagogical competence is the main competency that must be possessed by teachers and begins to be learned by every prospective teacher since they study at higher education level. Much of higher education research has forgotten the sustainability of this competency and has put more emphasis on competence in understanding learning content, even though a learning innovation is needed that makes this competency continue so that it is not just theory but practice for prospective teachers. Therefore, this research was conducted with the aim of looking at the responses of students (prospective elementary school teachers) to the usefulness and sustainability of learning innovations that have been carried out through the RADEC (Read-Answer-Discuss-Explain-Create) learning model in order to increase these pedagogical competencies. The research was conducted through a qualitative descriptive method, using data collection techniques through a survey method. The study involved 144 respondents. The data obtained revealed that the majority of students gave a positive response to the RADEC learning process in order to increase their pedagogical competence. Thus, it is hoped that the results of this research can become material for practical reflection for education practitioners to be able to redevelop the RADEC learning model, especially in the context of increasing teacher pedagogical competence in addition to increasing learning content competencies.